Formation of an inclusive urban environment based on the Principles of universal design: theoretical and practical Experience of Norway (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The article provides a comprehensive scientific analysis of the concept of UniversalDesign as a fundamental tool for shaping a modern inclusive urban environment. Based on thestudy of Norway’s leading expertise, the mechanisms for transforming theoretical principles ofarchitectural barrier-free design into practical spatial solutions are investigated. The author exploresthe essence of the seven fundamental principles of Universal Design, emphasizing aspects such asequitable use, flexibility, intuitiveness, and low physical effort.A number of landmark objects are examined, including the Oslo Opera House, SchandorffSquare, and revitalized industrial complexes. These examples demonstrate the implementation of"seamless space," multimodal navigation, and cognitive accessibility. Particular attention is paid tothe socio-economic efficiency of universal planning and its role in stimulating urban mobility. Inthe context of the current challenges facing Ukraine, the necessity of implementing Norwegian"Design for All" standards into post-war reconstruction strategies is justified.The author argues that Universal Design is not only a requirement for social justice but alsoan effective instrument for increasing the capitalization of the architectural environment andfostering a democratic society where every citizen is granted equal rights to a comfortable and safelife.For Ukraine, in the context of the global challenge of large-scale post-war reconstruction,Norway's experience is of strategic significance. Today, Ukraine faces a unique opportunity toachieve a civilizational transition from outdated post-Soviet standards of 'nominal accessibility' —which often existed only declaratively — to the creation of cities where every individual feels like afull participant in social life.The Norwegian path convincingly demonstrates that universal design is not a financial burdenon a project, but rather serves as an effective tool for enhancing the quality and capitalization of thebuilt environment. Integrating inclusive solutions directly into the 'genetic code' of architecturalprojects is the most promising development vector for the recovery of Ukrainian cities, enabling theformation of an equitable, safe, and open society of the future.
Keywords: universal design; inclusive city; architectural morphology; urban mobility; revitalization